Early compliance with IFRS 16, earnings management, and corruption: evidence from Southeast Asia - Fuad Fuad; Agung Juliarto; Andrian Budi Prasetyo; Ali Riza Fahlevi (Cogent Business & Management, 2022)
The primary purpose of this paper is twofold: firstly, to investigate the effect of early compliance with International Financial Reporting Standards 16 on Leases on earnings management and firm performance; secondly, to examine the moderating roles of corruption environment on those relationships. We test our hypotheses by investigating 1071 industrial firms in Southeast Asian countries, including Indonesia, Malaysia, Singapore, Thailand, and Vietnam using multivariate analyses. Our findings suggest that companies with lower governance mechanisms and looser institutional backgrounds are more likely to find that IFRS implementation may provide less room for management to maximize their short-term gain by manipulating earnings. Nevertheless, we do not find a similar pattern among the firms with low corruption culture. We also observe that firms' performance in high corruption culture imposing early implementation of IFRS 16 is significantly higher than firms in low corruption culture. The results provide valuable input to the standard setters and regulators to consider the importance of a strong institutional framework in ensuring IFRS's effective implementation.
Keywords: 650; financial performance; earnings management; corruption; ASEAN; voluntary/mandatory adoption of IFRS